Aktivitas BSLT Fraksi Daun dan Gall Syzygium guineensis: Studi Komparatif - Marliza, Hesti; De Nanda Herru, Yoan; Yelmiza, Yelmiza; Surya, Alfin (Journal of Research and Education Chemistry, 2025)
This study investigates the Brine Shrimp Lethality Test (BSLT) activity of leaf and gall fractions of Syzygium guineensis, a plant known for its traditional medicinal properties. The objective is to evaluate the cytotoxic potential of these fractions using BSLT, which is a reliable method for assessing toxicity. Leaf and gall samples were extracted using n-hexane, ethyl acetate, and ethanol-water solvents. The cytotoxicity was quantified by determining the LC50 values for each fraction. The results indicated that the leaf fractions exhibited LC50 values of 29.45 ppm (n-hexane), 28.33 ppm (ethyl acetate), and 30.57 ppm (ethanol-water). For the gall fractions, the LC50 values were 27.80 ppm (n-hexane), 26.61 ppm (ethyl acetate), and 24.95 ppm (ethanol-water). All fractions demonstrated significant cytotoxic activity, categorizing them as highly toxic. This study highlights the potential of both leaf and gall fractions of Syzygium guineensis as sources of cytotoxic agents, warranting further investigation for therapeutic applications.